Manajemen Mual dan Muntah pada Primigravida dengan Hiperemesis Gravidarum: Nausea and Vomiting Management in Primigravida with Hiperemesis Gravidarum - Adellia Dwi Ayu Pamungkas; Eka Adimayanti (Jurnal Keperawatan Berbudaya Sehat, 2025)
Pregnancy is the result of a fertilization between the egg and the spermatozoa (conception) which will be followed by physiological and psychological changes. During pregnancy, there are several problems, one of them is nausea that is often experienced in pregnant women which is also one of the symptoms in early pregnancy. The symptoms of nausea and vomiting by pregnant women are called hyperemesis gravidarum (HEG). Nutrition is very important during pregnant, nutritional disorders are included in the period that determines the quality of growth and development of the fetus to be born where during pregnancy determines the state of the fetus in the mother's womb. Provide an overview of nausea and vomiting management in primigravida with hyperemesis gravidarum. This is descriptive research with case study using nursing care approach include assessment, nursing diagnosis, intervention and evaluation. After 3 days of management, the problem of nausea and vomiting management in primigravida with hyperemesis gravidarum was partially solved. The next intervention is educational to eat little but often and in a warm state. It is hoped that primigravida pregnant women who experience hyperemesis gravidarum can manage nutrients by eating little but often, serving food in a warm state, staying away from things that stimulate feelings of nausea and vomiting.